Schwannoma of the Caruncle: A Rare Tumour - Abhaypal, Khushdeep; Singh, Manpreet; Saini, Manu; Gupta, Kirti; Dhiman, Rajneesh; Gupta, Pankaj (Nepalese Journal of Ophthalmology, 2024)
Introduction: Schwannomas, typically benign, encapsulated tumours arising from peripheral nerve sheaths, are commonly found in the orbit but are exceptionally rare in the caruncle. Here, a unique case of caruncular schwannoma is reported in an adolescent male who presented with gradual, painless swelling over a two-year period. This rarity emphasises the need to consider schwannomas in the differential diagnosis of caruncular masses. Case: An 18-year-old male presented with a two-year history of progressively enlarging swelling adjacent to the right lacrimal caruncle, without associated symptoms or trauma. The mass was completely excised under local anaesthesia. Observation: Histopathological analysis revealed a well-defined tumour consisting of spindle cells. Immunohistochemical staining for S-100 was strongly positive, confirming the diagnosis of schwannoma. This case is the first documented instance of caruncular schwannoma in a young individual, contributing to the limited understanding of this condition. Conclusion: This case highlights a rare presentation of caruncular schwannoma in an adolescent male, marked by a painless, progressively enlarging mass adjacent to the right lacrimal caruncle over a two-year period. Complete excision under local anaesthesia allowed for histopathological confirmation of schwannoma, with immunohistochemical positivity for S-100. Post-operative healing was uneventful, providing an excellent cosmetic result with no recurrence observed at the two-year follow-up.